1998
DOI: 10.1103/physrevlett.81.3908
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Epoxide: Unexpected Intermediate during Silicon Oxide Formation

Abstract: Infrared absorption spectroscopy and density functional cluster calculations are used to identify the intermediate oxide structures formed by high temperature annealing of the water-exposed Si͑100͒-͑2 3 1͒ surface. We find that initially there is a strong tendency for oxygen to agglomerate on single dimer units at T ϳ 800 K. Upon dehydrogenation, a remarkable structural transition is observed, wherein the dangling bonds recombine to form silicon epoxides (three-membered Si-O-Si rings). We demonstrate that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 13 publications
7
106
1
Order By: Relevance
“…4.15b). This behaviour points to higher amount of defects due to stress at the Si(111)/SiO 2 interface than for the Si(100)/SiO 2 and Si(311)/SiO 2 interfaces, which can be expected due to better Si-O-Si bond angle alignment at the interface for (100) and (311) orientation of Si as compared to the Si(111) [47][48][49][50][51]. Even during oxidation, is higher when current oscillations at +8 V occur at the Si(100) surface.…”
Section: Oxidation/hydrogenation Cyclesmentioning
confidence: 84%
“…4.15b). This behaviour points to higher amount of defects due to stress at the Si(111)/SiO 2 interface than for the Si(100)/SiO 2 and Si(311)/SiO 2 interfaces, which can be expected due to better Si-O-Si bond angle alignment at the interface for (100) and (311) orientation of Si as compared to the Si(111) [47][48][49][50][51]. Even during oxidation, is higher when current oscillations at +8 V occur at the Si(100) surface.…”
Section: Oxidation/hydrogenation Cyclesmentioning
confidence: 84%
“…The reaction of water with a Si(1 0 0) surface has been studied by an IR external transmission (ET) method and by ab initio quantum chemical cluster calculations, which clearly establish that there is not a barrier to dissociative chemisorption of H 2 O on a Si(1 0 0)-(2 · 1) surface and leads to the formation of stable Si-H and Si-OH bands on the same Si-Si dimer unit [2]. Further annealing induces the insertion of oxygen atoms into the Si back bonds or the formation of epoxides through dehydrogenation [3,4]. Recent STM studies concerning the C-defect on the Si(1 0 0) have shown that water dissociates on two adjacent dimers and/or the same dimer [9,10].…”
Section: Introductionmentioning
confidence: 87%
“…In the model systems, the dangling bonds of Si atoms other than the top silicon atoms were terminated by tritium atoms to avoid artifacts due to excess spin or charge. Unlike reported theoretical methods in which the third and forth layer silicon atoms were fixed at the ideal bulk crystalline positions [2][3][4][5]7], all the atoms of the clusters in this study were allowed to fully relax without constraints. Termination with tritium atoms was very effective in localizing all the surface vibrations, which eased the assignments of the calculated vibrational modes.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations